Environmental Sampling and Analysis (Field and Laboratory Works) - Mimi Suliza Muhamad, (2025)
This book provides hands-on activities related to environmental sampling and analysis, designed for students in the Bachelor of Civil Engineering Technology (Environment) program at UTHM. Each chapter focuses on different field and experimental works. The first chapter covers water sampling, followed by the second chapter on water quality analysis. The third chapter discusses soil sampling, while the fourth chapter focuses on soil quality analysis. Chapter five explores air sampling, and the sixth chapter presents air quality analysis.